Multidrug-Resistant Bacteria in Fresh Fruit Juices Sold in Benghazi, Libya - Monia A. BaLshikh; Ismaeel H. Bozakouk (Libyan Journal of Science &Technology, 2026)
Antimicrobial resistance (AMR) is a major global public health threat, particularly in ready-to-consume foods produced under informal urban conditions. Fresh fruit juices may serve as reservoirs and transmission vehicles for multidrug-resistant (MDR) bacteria, posing a significant potential risk to community health. A cross-sectional study was conducted on 128 fresh strawberry and mango juice samples, randomly collected from 16 cafés in Benghazi, Libya. Bacterial identification was performed using standard techniques described in Bergey’s Manual of Systematic Bacteriology. Antimicrobial susceptibility testing and MDR prevalence were assessed using the Kirby–Bauer disk diffusion method according to CLSI M100, 31st edition (2021), against 11 commonly used antibiotics: amoxicillin, amikacin, clarithromycin, ciprofloxacin, imipenem, oxacillin, cefixime, cephalexin, doxycycline, cefuroxime, and sulfamethoxazole–trimethoprim. The evaluation of bacterial contamination revealed that 110(94.02%) isolates were Gram-negative, comprising 95 (86.4%) Enterobacteriaceae and 15(13.6%) non-Enterobacteriaceae, whereas 7(5.98%) isolates were Gram-positive bacteria. Antimicrobial susceptibility testing showed that Gram-negative isolates exhibited high resistance to amoxicillin–clavulanate (61%), oxacillin (61%), and clarithromycin (50%), complete susceptibility to doxycycline (0%) and ciprofloxacin (0%), and moderate resistance to cephalosporins (10–12%). Enterobacteriaceae displayed similar resistance patterns, with 61% resistant to amoxicillin–clavulanate, 61% to oxacillin, and 50.5% to clarithromycin. Non-Enterobacteriaceae showed 20% resistance to imipenem and amikacin, while remaining fully susceptible to ciprofloxacin, doxycycline, and sulfamethoxazole–trimethoprim. Gram-positive bacteria exhibited complete resistance to ciprofloxacin (100%), high resistance to clarithromycin (100%) and amoxicillin–clavulanate (57%), moderate resistance to cephalosporins (36%), and full susceptibility to doxycycline (0%). MDR prevalence and mean MAR indices were calculated for each group: Gram-positive bacteria exhibited 100% MDR with a mean MAR of 0.45; Gram-negative isolates showed 87.3% MDR with a mean MAR of 0.29; Enterobacteriaceae had 89% MDR with a mean MAR of 0.27; and non-Enterobacteriaceae displayed 100% MDR with a mean MAR of 0.55. Several isolates corresponded to WHO Critical Priority Pathogens, including carbapenem-resistant Enterobacteriaceae and non-Enterobacteriaceae, ESBL-producing Enterobacteriaceae, and methicillin-resistant Gram-positive bacteria (MRSA). These findings indicate that fresh juices in urban informal settings may act as reservoirs and transmission vehicles for MDR bacteria. The results emphasize the urgent need for improved food hygiene, routine microbiological surveillance, and One Health interventions to prevent the spread of multidrug-resistant pathogens in the community.